Fibonacci Number plus Constant in terms of Fibonacci Numbers

From ProofWiki
Jump to navigation Jump to search

Theorem

Let $c$ be a number.

Let $\sequence {b_n}$ be the sequence defined as:

$b_n = \begin{cases}

0 & : n = 0 \\ 1 & : n = 1 \\ b_{n - 2} + b_{n - 1} + c & : n > 1 \end{cases}$


Then $\sequence {b_n}$ can be expressed in Fibonacci numbers as:

$b_n = c F_{n - 1} + \paren {c + 1} F_n - c$


Proof

The proof proceeds by induction.

For all $n \in \Z_{\ge 0}$, let $\map P n$ be the proposition:

$b_n = c F_{n - 1} + \paren {c + 1} F_n - c$


Basis for the Induction

$\map P 0$ is the case:

\(\ds c F_{-1} + \paren {c + 1} F_0 - c\) \(=\) \(\ds \paren {-1}^0 c F_1 + \paren {c + 1} F_0 - c\) Fibonacci Number with Negative Index
\(\ds \) \(=\) \(\ds c \times 1 + \paren {c + 1} \times 0 - c\) Definition of Fibonacci Number: $F_0 = 0, F_1 = 1$
\(\ds \) \(=\) \(\ds 0\)
\(\ds \) \(=\) \(\ds b_0\) by definition

Thus $\map P 0$ is seen to hold.


$\map P 1$ is the case:

\(\ds c F_0 + \paren {c + 1} F_1 - c\) \(=\) \(\ds c \times 0 + \paren {c + 1} \times 1 - c\) Definition of Fibonacci Number: $F_0 = 0, F_1 = 1$
\(\ds \) \(=\) \(\ds 1\)
\(\ds \) \(=\) \(\ds b_1\) by definition

Thus $\map P 1$ is seen to hold.


This is the basis for the induction.


Induction Hypothesis

Now it needs to be shown that, if $\map P {k - 1}$ and $\map P k$ are true, where $k \ge 1$, then it logically follows that $\map P {k + 1}$ is true.


So this is the induction hypothesis:

$b_{k - 1} = c F_{k - 2} + \paren {c + 1} F_{k - 1} - c$
$b_k = c F_{k - 1} + \paren {c + 1} F_k - c$


from which it is to be shown that:

$b_{k + 1} = c F_k + \paren {c + 1} F_{k + 1} - c$


Induction Step

This is the induction step:


\(\ds b_{k + 1}\) \(=\) \(\ds b_{k - 1} + b_k + c\) by definition
\(\ds \) \(=\) \(\ds \paren {c F_{k - 2} + \paren {c + 1} F_{k - 1} - c} + \paren {c F_{k - 1} + \paren {c + 1} F_k - c} + c\) Induction Hypothesis
\(\ds \) \(=\) \(\ds c \paren {F_{k - 2} + F_{k - 1} } + \paren {c + 1} \paren {F_{k - 1} + F_k} - 2 c + c\)
\(\ds \) \(=\) \(\ds c F_k + \paren {c + 1} F_{k + 1} - c\) Definition of Fibonacci Number

So $\map P {k - 1} \land \map P k \implies \map P {k + 1}$ and the result follows by the Principle of Mathematical Induction.


Therefore:

$\forall n \in \Z_{\ge 0}: b_n = c F_{n - 1} + \paren {c + 1} F_n - c$

$\blacksquare$


Sources